Barometric and magnetic observations of vertical acoustic resonance and resultant generation of field-aligned current associated with earthquakes - Iyemori, Toshihiko (2013)
Three rare occasions are introduced, where the excitation of vertical acoustic resonance between the ground and the ionosphere, and the resultant generation of a field-aligned current, just after earthquakes are observationally confirmed. In the case of two inland earthquakes, barometric observations very close to the epicenters (i.e., only 30 km apart) were available, and they showed a sharp spectral peak which appeared within one hour after the origin time and lasted a few hours. The observed periods of the spectral peaks around 260 seconds are close to the period of the theoretically-expected fundamental mode of the resonance. On the other hand, magnetic observations on the ground showed a dominant period at 220–230 seconds which corresponds to the first overtone among theoretically-expected major resonance peaks. In the third case, i.e., during the 2010 Chile earthquake, a long-period magnetic oscillation in the east-west direction, which has two major resonance periods at 265 and 190–195 seconds, was observed on the night-side magnetic dip equator in Peru, where the distance is more than 2600 km from the epicenter, under a very quiet geomagnetic condition. The oscillation was interpreted as the effect of field-aligned current generated through a dynamo process in the ionosphere over the epicenter caused by the resonance.